Correction of Evanescent Wave Influence on the Flexural Wave Velocity and Wavelength Estimation Based on a Mode Shape Function - PANTELIĆ, Filip; ŠUMARAC PAVLOVIĆ, Dragana; MIJIĆ, Miomir; RIDLEY-ELLIS, Daniel (Archives of Acoustics, 2022)
The aim of this research is to use a simple acoustic method of a very near field recording, which enables measurement and display of oscillation modes, to estimate the velocity of flexural waves, based on the wavelengths of standing waves measured on the sample. The paper analyses cases of 1D geometry, flexural waves that occur on a beam excited by an impulse. Measurements were conducted on two different samples: steel and a wooden beam of the same length. Due to the appearance of evanescent waves at the boundary regions, the distance between the nodes of standing waves that occur deviates from half the wavelength, which can be compensated using a correction factor. Cases of fixed and free boundary conditions were analysed. By quantifying how much the boundary conditions change the mode shape function, it can be predicted how the mode of oscillation changes if the boundary conditions change, which can also find application in musical acoustics and sound radiation analysis.